(untitled) (The Research of Medical Science Review, 2025)
Background: Clubfoot is a common congenital deformity that is often treated using the Ponseti method, which includes Achilles tenotomy. The choice of anesthesia general or local during the procedure may influence the duration of the surgery, recovery time, and overall patient outcomes. Objective: To evaluate and compare the clinical outcomes of Achilles tenotomy in clubfoot patients treated by the Ponseti method, performed under general anesthesia versus local anesthesia. Methods: This Randomized Controlled Trial was conducted at Department of Orthopedics, Ayub Teaching Hospital Abbottabad from September 2023 to February 2024. Data were collected through Non-probability consecutive sampling. Baseline demographic data, including age, gender, and weight, were collected for each patient. Informed consent was obtained from the parents, explaining the potential risks and benefits of the study. The patients were then randomly assigned to one of two groups using blocked randomization. Results: The mean duration of the procedure was significantly shorter in Group A (18.5 ± 4.2 minutes) compared to Group B (28.3 ± 5.1 minutes, p < 0.01). The duration of hospitalization was also significantly shorter in Group A (6.2 ± 1.3 hours) compared to Group B (18.4 ± 2.2 hours, p < 0.01). Postoperative complications were minimal, with only one case of mild erythema in the local anesthesia group and two cases of mild vomiting in the general anesthesia group. Parental satisfaction was higher in Group A (93.3%) compared to Group B (83.3%), although this difference was not statistically significant (p = 0.32). Conclusions: It is concluded that Achilles tenotomy under local anesthesia is a viable and effective alternative to general anesthesia for clubfoot patients treated by the Ponseti method. Local anesthesia resulted in significantly shorter procedure times and reduced hospitalization, without compromising the correction outcomes or safety.